Control for systems with prescribed performance guarantees: An alternative interval theory-based approach. (December 2022) - Guo, Zongyi; Henry, David; Guo, Jianguo; Wang, Zheng; Cieslak, Jérôme; Chang, Jing
Abstract: This paper investigates the issue of control design for a class of nonlinear systems with guaranteed prescribed performance. Different from the existing prescribed performance control approaches, a switching control scheme is introduced to ensure that the errors do not violate the performance bound functions. Bounded stability is proved by means of the cooperative systems theory. It is shown that the proposed control paradigm establishes a unified prescribed performance control framework which covers bounded, asymptotic, finite and fixed-time stabilities, only by assigning adequately the performance bound functions. An inverted pendulum example demonstrates the effectiveness of the proposed approach.